Clustering Model for OKU Timur Script Images - Toriko, Liu; Purnamasari, Susan Dian; Kunang, Yesi Novaria; Yadi, Ilman Zuhri; Andri, Andri (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2025)
Abstract— The OKU Timur is a regency located in South Sumatra Province. In the OKU Timur region there are many historical heritage sites, one of which is the script. In general, script is a system of symbols for writing language. The OKU Timur script is a writing system that is usually used by the local community. This writing system is characterized by its unique characters and has high historical and aesthetic value for the local community. The OKU Timur script is used in daily communication, traditional ceremonies, historical documents, and various other cultural contexts. This research aims to develop a clustering model that is used to efficiently and accurately group Of OKU Timur script images based on certain characteristics. By using techniques in the field of clustering such as the K-Means algorithm this model is developed so that the clustering of OKU Timur script images is made automatically in order to save time and effort. The study employs the K-Means algorithm to divide the data into several clusters, grouping data with similar characteristics into one cluster and data with different characteristics into another. This research is also expected to contribute to preserving digital culture so that the development of OKU Timur characters can be passed on to future generations.Keywords— OKU Timur Script, Clustering, K-Means